Epidemiology of bovid fasciolosis in Larut and Matang, Perak, Malaysia - Che Kamaruddin, Naim (2022)
Fasciolosis is considered as an emerging neglected tropical disease that is threatening ruminant productivity and is zoonotic. In previous study, the Taiping abattoir showed the highest fasciolosis occurrence compared to the other investigated main abattoirs in Peninsular Malaysia, which could impede the government's initiatives to promote ruminant production in the region. Therefore, this study intended to describe the epidemiology of bovid fasciolosis in Larut and Matang (Taiping), Perak (LM) to initiate the effort to control fasciolosis which could drive to economic loss. A total of 371 faecal samples from bovid (dairy cattle, beef cattle, buffalo) from 23 selected farms were examined in this cross-sectional study from February until August 2020. Animals and farms detail were recorded, and a questionnaire has been completed by the farmers to collect data of risk factors during the farm visit. The coproscopical examination of faecal samples to record the Fasciola faecal egg count (fec) using FlukefinderÒ sedimentation was performed and the co-infection with Paramphistomes was observed. The correlation of Fasciola fec with Paramphistomes fec in co-infected bovids and also with Fasciola coproantigen concentration were correlated using Spearman correlation test. Heatmap density was used to interpolate the selected risk factors to visualise the fasciolosis exposure areas in LM. For the result, overall prevalence of bovid fasciolosis in LM was observed 36.9% (n=137/371). A total of 65.2% visited farms (n=15/23) having at least one case of bovid fasciolosis. Significant risk factors (p<0.05) for bovid fasciolosis in LM were buffalo (OR=9.5), bovid age more than three years (OR=5.5), body condition score lower than 5 (OR=1.2-14.9), larger grazing range (OR=1.3), more than one ruminant species in the farm (OR=2.0-2.1), extensive housing system (OR=4.0), increasing farm age (OR=1.2), and co-infection with Paramphistomes (OR=1.4). Fasciola and Paramphistomes fec in co-infected bovids was having a significant moderate positive correlation (r=0.36, p<0.01). Besides, Fasciola fec to Fasciola coproantigen concentration was also having significant moderate positive correlation (r=0.55, p<0.01). The exposure areas to fasciolosis in this study showed higher exposure in the northern LM compare to the central LM. Thereby, this study revealed moderate prevalence of bovid fasciolosis in LM and factors of host intrinsic, farm management, and co-infection with Paramphistomes are significantly associated with bovid fasciolosis in LM. The positive correlation of Fasciola and Paramphistomes in co-infected bovid could provide the predictive basis for bovid fasciolosis from the Paramphistomes occurrences. Besides, Fasciola coproantigen concentration could be useful in monitoring Fasciola eggs shedding to initiate targeted treatment of fasciolosis, however need further study for the application of coproantigen ELISA for this insight. The areas of high fasciolosis exposure in LM is beneficial to conduct control programmes to sustain the bovid production and welfare. The outcomes of this study are advantageous towards the understanding of the epidemiology of local bovid fasciolosis which is important in veterinary and public health.